Media Film: Experimental Example of Rasulullah Saw in Establishing Court Character - Ijah Siti Khodijah; M. Sidqi Falih As'ad; Alfiah Khodijah; Najah Adawiyah; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Character at this time becomes one of the parameters for the quality of a nation. The young generation with character will be able to achieve high noble values of the nation and state, but at this time the young generation is experiencing an extraordinary moral and character crisis along with the development and progress of the Times. In this study, the study conducted a training of polite character of the Saint through the medium of the film Rasulullah saw. This Film is one of the most popular films in the world. To be able to achieve the above goals research using quantitative research with experimental research type. The population and sample in this study were 16 students of Class X. Data collection techniques using pretest and posttest tests. This film is one of the most popular films among the people of Indonesia. With the results t count > t table is the value of 3.167 > 2.145 and the value of Sig. (2-tails) < 0.05 which is 0.007 < 0.05.